När föräldrar separerar - en kvantitativ sekundäranalys - Sjöbeck,Glenn (2018)
The aim of this study was to examine whether the association between parental separation and worse outcomes existed among adolescents in the ninth grade in Skåne. More specifically the aim was to find out how the well-being differed between children with separated parents and children living with both their parents. In addition, this study also examined gender differences. The study is based on secondary data from Region Skåne, where all together 9143 individuals in the ninth grade participated in the survey 2016. The data was later analyzed using a bivariat analysis as a method. Results from the study shows that there is a significant association that those children with separated parents have poorer well-being than children living with both their parents. The study also shows that girls in general have poorer mental health and its worst for girls who have separated parents.
Keywords: Divorce; Separation; Adolescents; Well-being; Families